4 - A proteção social básica como direito humano: um olhar sobre Moçambique - Maria Elvira Carlos Chipe; Rosana Albuquerque; Maria José Núncio (Africa Development, 2025)
This article draws attention to the course of the different dynamics invested in the social protection system, as a fundamental and internationally recognized right: life, health, education, work, housing, healthy environment, among others, with a view to sustainable development in nations. Through an exploratory and descriptive research, the article aims to bring a critical approach to the Mozambican social protection system, where, initially, we perceive social protection as a model based on the mutual recognition of the other as a social being and endowed with rights, where neighbourhood networks, kinship and/or even small social groups, share the philosophy of sharing and/or mutual help (exchange of goods and services). This social protection system, although informal, ensured in Mozambique, over several years, some social and economic stability for families, particularly those in need. In another aspect, we will approach social protection as an inalienable right, in which the governance, in its mission, has the entire responsibility of guaranteeing the full enjoyment of the resources and opportunities that will allow the individual to develop capacities and skills in view of social well-being. In conclusion, we will have an overview of the efforts that the Mozambican State, within the scope of international agreements, undertakes for a more effective and understanding social protection.